Psychosocial Impact of Epilepsy in Older Adults - Manacheril, Rinu (Healthcare (Basel), 2015)
Objective: The purpose of our study was to describe the quality of life of older adults with seizures or epilepsy and compare its psychosocial impact between those who were new diagnosed and those diagnosed before the age of 65. Methods: In-depth face to face interviews with open ended questions were conducted with two participant groups: Incident group: 42 older adults (>65 years) with new onset or newly diagnosed after age of 65; and Prevalent group: 15 older adults (>65 years) diagnosed before age of 65. Interviews were reviewed and coded using a list of themes and results were compared between the two groups. Eight topics were selected from the participants’ responses to questions about the psychosocial impact of epilepsy and seizures. The topics were then analyzed and compared between the two groups. Results: The topics analyzed were: Emotional and physical impact, significant life changes, co-morbidities, information gathering, stigma, AED side effects, changes in relationships and attitude toward diagnosis. Conclusion: We concluded that the age at onset and duration does seem to have a negative correlation with health related quality of life. However, the perceived health status of older adults with chronic epilepsy was significantly better and reflected in their more positive approach to the diagnosis of seizures or epilepsy probably because they have had a longer opportunity to learn to cope with their diagnosis.